Influence the filler orientation on the performance of bipolar plate - Nabilah Afiqah Mohd Radzuan,; Abu Bakar Sulong,; Mahendra Rao Somalu, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Bipolar plates significantly contribute to the development of the polymer electrolyte membrane (PEM) fuel cells technology due to their ability to produce high electrical conductivity based on the type of materials used. Mismatching of inappropriate materials and manufacture may lead to the inferior performance of PEM fuel cells. Hence, material development was determined crucial to balance the overall performance of PEM fuels including the mechanical properties and electrical conductivity of the materials. Studies on conductive polymer composites (CPCs) offered filler with orientation in terms of filler with aspect ratio and shape as an alternative method to enhance the overall performance of the bipolar plate. Filler orientations permit an excellent conductivity network formation while controlling the filler alignment based on required applications. This paper reviewed various studies of filler orientations including materials used and methods of manufacture of CPC materials for the effective development of bipolar plate. The technique to orientate the filler was highlight in terms of materials processing and its effects on the materials performance.